2017
DOI: 10.1177/0269215517723056
|View full text |Cite
|
Sign up to set email alerts
|

The role of movement errors in modifying spatiotemporal gait asymmetry post stroke: a randomized controlled trial

Abstract: Augmenting errors was not superior to minimizing errors or providing only verbal feedback during conventional treadmill walking. Therefore, the use of verbal feedback to target spatiotemporal asymmetry, which was common to all participants, appears to be sufficient to reduce step length asymmetry. Alterations in stance time asymmetry were not elicited in any group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 36 publications
(77 reference statements)
4
87
0
9
Order By: Relevance
“…Moreover, we have shown that the extent to which movements are recalibrated varied greatly across post-stroke individuals. We speculate that individual differences in sensorimotor recalibration may explain why some stroke survivors improve their gait symmetry in response to repeated split-belt treadmill training while others do not (Reisman et al, 2013;Betschart et al, 2018;Lewek et al, 2018). If so, it may be possible to identify patients that will benefit from splitbelt training within just a single session.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, we have shown that the extent to which movements are recalibrated varied greatly across post-stroke individuals. We speculate that individual differences in sensorimotor recalibration may explain why some stroke survivors improve their gait symmetry in response to repeated split-belt treadmill training while others do not (Reisman et al, 2013;Betschart et al, 2018;Lewek et al, 2018). If so, it may be possible to identify patients that will benefit from splitbelt training within just a single session.…”
Section: Discussionmentioning
confidence: 98%
“…We do not intend for these findings to be interpreted as an indictment on step length asymmetry as a target of post-stroke gait rehabilitation. Interventions that target step length asymmetry have shown promise for improving gait speed 15 and decreasing cost of transport 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Many rehabilitation approaches aim to restore step length symmetry [10][11][12][13][14][15][16] . The rationale for restoring step length symmetry is multifaceted: 1) asymmetric stepping increases the cost of transport in healthy adults 17 , 2) persons post-stroke who walk with more asymmetric step lengths also tend to exhibit poorer balance 18 and more effortful gait patterns 19 , 3) step length is easy to measure and manipulate in clinical settings (e.g., "step to the lines on the floor"), and 4) step length asymmetry is a simple, discrete metric that manifests from complex kinematic and kinetic asymmetries that can be difficult to treat in isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…462 463 Incline split-belt training may be a promising way to augment locomotor and adaptation 464 and recalibration in the lesioned motor system. Not everyone who has had a stroke re-learns to 465 walk symmetrically following several weeks of flat split-belt training 466 Betschart et al 2018;Lewek et al 2018). Thus, it is clinically relevant to explore alternative 467 strategies to augment adaptation in survivors of stroke other than increasing the speed difference 468 We investigated the influence of propulsion demands during walking on the locomotor 477 adaptation and recalibration in the asymmetric motor system.…”
Section: Larger After-effects Of Propulsion Forces Split-belt Inclinementioning
confidence: 99%